2021
DOI: 10.1093/nop/npab039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative dexamethasone on survival, steroid dependency, and infections in newly diagnosed glioblastoma patients

Abstract: Background We examine the effect of dexamethasone prescribed in the initial 3 postoperative weeks on survival, steroid dependency, and infection in glioblastoma patients. Methods In this single-center retrospective cohort analysis, we electronically retrieved inpatient administration and outpatient prescriptions of dexamethasone and laboratory values from the medical record of 360 glioblastoma patients. We correlated total de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…Additionally, upon stratification into subgroups of dexamethasone intake (cumulative pre-operative, postoperative and perioperative (total) dexamethasone intake), we only observed total dexamethasone to be associated with OS. Interestingly, there was no significant correlation between cumulative dexamethasone dose and tumor volume or edema volume ( eFigure 2a in the supplements ), which is in contrast to the observation from Zhou and colleagues for glioblastoma 17 . Limitations of this study include the retrospective nature of the data originating from a retrospective and prospective brain metastasis registry.…”
Section: Discussion/conclusioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Additionally, upon stratification into subgroups of dexamethasone intake (cumulative pre-operative, postoperative and perioperative (total) dexamethasone intake), we only observed total dexamethasone to be associated with OS. Interestingly, there was no significant correlation between cumulative dexamethasone dose and tumor volume or edema volume ( eFigure 2a in the supplements ), which is in contrast to the observation from Zhou and colleagues for glioblastoma 17 . Limitations of this study include the retrospective nature of the data originating from a retrospective and prospective brain metastasis registry.…”
Section: Discussion/conclusioncontrasting
confidence: 84%
“…Here, the sum of cumulative dexamethasone doses in the pre-operative and post-operative period seems to have impact on OS as reported previously. For instance, Zhou et al demonstrated in a single-center PSM study that postoperative day (POD) 0 to 21 dexamethasone dosage correlated with overall survival 17 . Interestingly, Medikonda et al recently showed that that pre-operative, but not post-operative or pre- and postoperative Dexamethasone dosage in Glioblastoma patients was linked to shorter OS and reported a hazard ratio of 3.0 (95% CI: 0.9-9.4).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…48 Other deleterious effects of dexamethasone on infection risk, lymphopenia, metabolic disturbances, thromboembolism risk, muscle wasting, and diminished performance status may also contribute to diminished survival. 49,50 Nevertheless, in this cohort of patients, the deleterious impact of corticosteroid use by multivariate analysis was less than half of the impact of PPI use.…”
Section: Discussionmentioning
confidence: 66%
“…After screening all the abstracts, 153 studies were retrieved for full review. After the exclusion of ineligible studies, 22 studies were identified for the quantitative review [17,18,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%